Right ventricular endomyocardial fibrosis: Atypical presentation of a rare disease. Case report - López Gutiérrez, Laura Valentina (2024)
Endomyocardial fibrosis or Davies disease is a rare cause of restrictive cardiomyopathy. It is characterized by the deposit of fibrous material in the endocardium that leads to quickly progressive heart failure. It most frequently affects both ventricles, with isolated involvement of the right ventricle being the least common form. The clinical presentation of this entity is based on symptoms of right heart failure, although arrhythmias and conduction disorders may also be present. The treatment is determined by the management of congestion and surgical intervention in symptomatic patients. We present the first case of endomyocardial fibrosis isolated from the right ventricle in Colombia, we describe the clinical, etiological, imaging and management characteristics in order to deliver to the medical community an approximate understanding of this disease focusing on an unusual way of presentation.